Digital competence in teachers of health sciences in a private university in lima - Trujillo, María de los Ángeles Sánchez (2021)
Introduction: This work responds to the need of developing digital skills in teachers, who can take advantage of the different potentialities of technological resources in order to achieve better learning in their students. Objective: To determine the differences between the dimensions of the digital competence of teachers of the School of Health Sciences of a private university in Lima, Peru, according to sociodemographic variables. Methods: A comparative descriptive design was used. It should also be noted that a total population composed of 40 teachers was considered, of which 34 agreed to collaborate in the research. The instrument used to collect information was an adaptation of the Teaching Digital Competence Questionnaire, prepared by Javier Tourón, Deborah Martín, Enrique Navarro, Silvia Pradas and Victoria Íñigo in 2018. In addition, a sociodemographic record was addressed to teachers. Subsequently, statistical analysis was performed using the SPSS 25 software. Results: It was found that there were no significant differences between the dimensions of digital competence, according to the sociodemographic variables of sex, age, maximum level of study reached, and years of teaching experience. Even so, the differences evidenced in some of these variables could be subject of future studies. Conclusions: The dimension in which teachers have the greatest problems is security, while the one in which they have the least difficulties is problem solving.